Izvleček brazilske kreše (Acmella oleracea) v pomlajevalni kozmetiki - Schoss, Katja (Farmacevtski vestnik, 2023)
Distinct changes in the appearance of the skin, including the appearance of wrinkles as the most obvious sign of skin ageing, have a significant impact on an individual's self-esteem. Thus, we have a wide selection of cosmetic products and procedures on the market today that improve the appearance of mature skin or wrinkles, and cosmetic science also deals intensively with cosmetically active ingredients of plant origin in this area. In the research, we produced a placebo and a test emulsion with an extract of para cress (Acmella oleracea). We evaluated their performance on volunteers using the method of hedonic sensory evaluation with effective testing, focusing on the visible effects of reducing eye wrinkles. The emulsion with para cress extract showed an improved wrinkle condition after two months of use, however, the effect was not statistically significant.
Keywords: Acmella oleracea; anti-age učinek; brazilska kreša; Kozmetika